Alpha Taxonomy of Eocene Primates from the Great Divide Basin, Wyoming - Pavell, Dakota R (East Carolina University, 2021)
The identification of the alpha taxonomy of an extinct species is the first step towards understanding its evolutionary history and relationships with other organisms. Alpha taxonomy refers to the initial classification of the specimen based on the analysis of the observable morphological traits. Traditionally paleoprimatologists, paleobiologists, and paleoanthropologists have conducted morphological examinations via visible observations or with the use of a microscope. However, technological advances have resulted in the ability to accurately examine and describe small structures that have been historically difficult to study. This project used a micro computed tomography (CT) scanner to examine the dental morphology of eleven Nothartcine primates including ten specimens from the genus Cantius and one specimen from the genus Copelemur. Scanned images were imported into Avizo, a three-dimensional visualization software, to generate digital reconstructions. The digital reconstructions were used for further morphological analyses to aid in the identification of the taxonomic classifications of the study specimens. The three-dimensional reconstructions of the specimens support the existing alpha taxonomy of the Nothartcine primates. The employment of the CT scanner revealed small variations in the dental morphology of the study specimens which may be attributed to inter-individual differences, dental wear patterns, or evolutionary changes through time.
Keywords: Dental Morphology; Primates--Evolution--Wyoming--Great Divide Basin; Extinct animals--Wyoming--Great Divide Basin; Paleontology--Eocene